2016
DOI: 10.1037/abn0000152
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotionality and its facets moderate the effects of exposure to Hurricane Sandy on children’s postdisaster depression and anxiety symptoms.

Abstract: According to diathesis-stress models, temperament traits, such as negative emotionality (NE), may moderate the effects of stressors on the development of symptoms of psychopathology, although very little research has tested such models in children. Moreover, there are few data on whether specific facets of NE (sadness, fear, or anger) may specifically moderate the effects of stress on depression versus anxiety. Finally, there is a paucity of research examining whether childhood temperament moderates the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 56 publications
(113 reference statements)
5
54
1
Order By: Relevance
“…Adjusting for pre-Sandy symptoms, higher levels of stress from Hurricane Sandy predicted elevated levels of anxiety symptoms, but only in children characterized by increased temperamental fear measured 7 years prior to the hurricane when children were 3 years old. 9 These findings support a diathesis-stress model, suggesting that temperament plays an important and enduring role in the development of psychopathology in the context of stressful life events.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Adjusting for pre-Sandy symptoms, higher levels of stress from Hurricane Sandy predicted elevated levels of anxiety symptoms, but only in children characterized by increased temperamental fear measured 7 years prior to the hurricane when children were 3 years old. 9 These findings support a diathesis-stress model, suggesting that temperament plays an important and enduring role in the development of psychopathology in the context of stressful life events.…”
Section: Introductionsupporting
confidence: 65%
“…9,36,37 The items were drawn from previous questionnaires developed for Hurricane Katrina 38 and Hurricane Ike. 39 The first 8 items were rated on a 5-point scale (1 = not at all affected, 5 = extremely affected), and included damage to home, safety threatened, financial hardship, children fear for their safety, life disrupted by the hurricane, difficulty finding gasoline, difficulty getting food, water, or warmth, and children quarreling or complaining more than usual.…”
Section: Methodsmentioning
confidence: 99%
“…For example, adult data from the Zurich Cohort Study ( n = 591) indicates that a one standard-deviation increase in dispositional negativity at the time of the baseline assessment in 1988 increased the odds of developing a major depressive episode by 41% and an anxiety disorder by 32% during the twenty year (1988–2008) follow-up period (Hengartner, Ajdacic-Gross, Wyss, Angst, & Rossler, 2016). These relations are particularly evident among individuals exposed to stress and negative life events (e.g., childhood maltreatment; Kopala-Sibley et al, in press; Kopala-Sibley et al, 2016; Vinkers et al, 2014), suggesting that high levels of dispositional negativity represent a diathesis for the internalizing spectrum of disorders (i.e., anxiety and depression). Among adults with a history of internalizing disorders, higher levels of dispositional negativity are associated with a greater number of co-morbid diagnoses (Hengartner, Kawohl, Haker, Rossler, & Ajdacic-Gross, 2016) and a more pessimistic prognosis (Berlanga, Heinze, Torres, Apiquian, & Cabellero, 1999; Duggan, Lee, & Murray, 1990; Faravelli, Ambonetti, Pallanti, & Pazzagli, 1986; Hirschfeld, Klerman, Andreasen, Clayton, & Keller, 1986; Kendler, Neale, Kessler, & Heath, 1993; Ormel, Oldehinkel, & Vollebergh, 2004; Quilty et al, 2008; Scott, Williams, Brittlebank, & Ferrier, 1995; Weissman, Prusoff, & Klerman, 1978).…”
Section: Elevated Dispositional Negativity Confers Heightened Risk Fomentioning
confidence: 99%
“…Personality traits have emerged as prospective predictors of health outcomes in the general population [5][6][7][8][9][10][11][12][13], over and above traditional predictors such as socio-economic status and IQ levels. Personality is also among top vulnerability and resilience factors in response to trauma and disasters [14][15][16][17]. Prospective studies revealed that vulnerable personality traits, such as neuroticism, may impede recovery from the health sequelae of traumas [18][19][20][21], while protective traits such as extraversion and conscientiousness can facilitate resilience to stress [22][23][24] and recovery if disorders occur [25][26][27].…”
Section: Introductionmentioning
confidence: 99%